A microstructure-based mechanism of cracking in high temperature hydrogen attack. (November 2017) - Martin, M.L.; Dadfarnia, M.; Orwig, S.; Moore, D.; Sofronis, P.
Abstract: High Temperature Hydrogen Attack (HTHA) of steels plagues higher temperature industrial applications, especially in the petrochemical industry, due to the lack of a mechanistic understanding of the phenomenon and the use of empirically established design criteria, such as the Nelson curves. By using advanced microscopy techniques to explore the microstructure immediately ahead of crack tips and along cavitated grain boundaries, we gained a better understanding of the physical processes occurring early during the HTHA damage process, which can guide the development of models for the degradation process accounting for methane formation and creep cavitation. The results confirm the fundamentals of previously proposed models, but also provide finer details than have been previously known. Based on the underlying deformation and grain boundary fracture, we propose a model for material failure underlying HTHA. Graphical abstract: Image